Fine-Tuning of Adipogenesis is a Potential Mechanism for Improved Insulin Sensitivity in Human Adipose Tissue with Rosiglitazone Therapy - Ahmed, Meftun; Karpe, Fredrik (Journal of Bangladesh Society of Physiologist, 2010)
Back ground: Adipose tissue plays a crucial role in regulation of lipid and carbohydrate metabolism and many of these actions are regulated by insulin. Objective: The present study aims to detect potential novel protein targets for insulin sensitization in human adipose tissue by using an unbiased proteomic approaches. Method: Ten moderately obese, but otherwise healthy, subjects were treated with rosiglitazone 4 mg BD for 14 days. Protein profiles were obtained by two-dimensional gel (2-DG) electrophoresis and protein spots were identified using tandem mass spectrometry. Data were analyzed statistically by using student's paired t test. Results: Proteomic analysis revealed distinct up or down regulation (≥ 2-fold) in 122 protein spots on the 2-D gel images between day 0 and day 14 adipose tissue samples. Treatment with rosiglitazone increased the expression of extracellular matrix proteins including collagens, galectin-1, nidogen-1 and laminin. Analysis revealed differential expression of several other proteins involved in redox regulation (ferritin light chain, heat-shock protein β-5, heatshock protein β-1), endoplasmic reticulum (ER) stress (endoplasmin, 78 kDa glucose-regulated protein precursor), cytoskeletal reorganization (lamin A/C, vimentin, tropomyosin-3, tropomyosin-4, gelsolin, actin tubulin β-1 chain), signaling (calmodulin), and others (glyceraldehyde-3-phosphate dehydrogenase, α enolase). Conclusion: Such orchestrated changes in expression of multiple proteins provide insights into the mechanism undarlying the increased efficiency in adipocyte remodeling and differentiation and hence improvement of insulin sensitivity in response to rosiglitazone treatment. Key words: Rosiglitazone, adipose tissue, proteomics, collagen, adipogenesis, insulin, electrophoresis, spectrometry. DOI: 10.3329/jbsp.v4i2.4170 J Bangladesh Soc Physiol. 2009 Dec;4(2): 34-43